EVALUATION OF INDIGENOUS DRUGS IN THE MANAGEMENT OF PCOD IN TEENAGE GIRLS - Bharathi, K.; Jain, C.M.; Pushpalatha, B. Dinesh (International Journal of Ayurveda and Pharma Research, 2015)
Polycystic ovarian disease is one of the most common gynecological disorders during puberty. This is otherwise known as Stein-Leventhal Syndrome and occurs due to the incorrect set of hypothalamo-pituitary homeostatic during puberty and characterized by oligomenorrhoea / amenorrhoea, delayed periods, hirsutism, hoarseness of voice etc. Based on the clinical features this can be compared with Alpartava /Artavakshaya as per the Ayurvedic classics. In Artavakshaya (deficiency of Artva), Rajasrava (menstruation) do not appear in its appropriate time or is delayed. Often gynecologists keep these patients on combination of estrogen and progesterone therapy. Exogenous hormonal treatment again disturbs the endogenous hormonal pattern and the pathology continues. In the present study an attempt has been made to find out safe alternate therapy to cure PCOD and regularize menstruation with Ayurvedic drugs. For the present study, Ashokarishtam is selected to improve Rajodhatu, Kanchanara guggulu and Varunadi kashayam are selected to regress cysts of the ovary. Study carried out in 52 number of teenage girls, out of which, 21 (42.86%) patients have shown Good Response, 10 (20.41%) cases have shown Fair response, 03 (06.12%) cases have shown Poor response, 15 (32.61%) did not show any response and 03 cases were dropped out from the study. On statistical analysis, efficacy of the trial drugs found highly significant in relieving PCOD (P<0.001).